Decentralization, Democracy, and Development - Yongmei Zhou (The International Bank for Reconstruction and D, 2009)
n 2004, the government of Sierra Leone opted for a rethink of its national governance arrangement by embarking on the resuscitation of democratically elected local government after 32 years experimenting with central government appointed district and municipal governments. The decision by the government and the people of Sierra Leone was driven by a primary consideration to address the countryâ€™s seeming nonperformance in the areas of citizensâ€™ participation in governance and responding to the needs of citizens as it relates to attainment of the Millennium Development Goals (MDGs) as well as ensuring poverty reduction in the country. The process of reintroducing the current and ongoing National Decentralization Program in the country assumed a partnership model involving the government of Sierra Leone, development partners and a host of national nonstate actors, especially civil society organizations. The path that was taken involved consultations and consensus building among the stakeholders on the design, structures and systems which culminated in the development of a comprehensive legislationâ€”the Local Government Act (2004). Since the commencement of the implementation of the â€œbig bangâ€ approach to the Decentralization Program in Sierra Leone, there has been a well planned mechanism for advancing the process in the political, administrative, functional, and fiscal areas. There has been a record of marked results, in particular, establishment of 19 local government entities in the country; two consecutive local government elections conducted in 2004 and 2008; and facilitation of a comprehensive national devolution program leading to core functions and responsibilities in health, education and agriculture being devolved to the local authorities with the attendant fiscal resources to assume and execute such responsibilities